2016
DOI: 10.1055/s-0042-117218
|View full text |Cite
|
Sign up to set email alerts
|

Semi-solid feeds may reduce the risk of aspiration pneumonia and shorten postoperative length of stay after percutaneous endoscopic gastrostomy (PEG)

Abstract: Background and study aims: Feeding-related adverse events after percutaneous endoscopic gastrostomy (PEG) such as aspiration pneumonia may result in prolonged hospitalization and postoperative mortality. This study evaluated the efficacy of using semi-solid feeds to reduce feeding-related adverse events and improve clinical outcomes. Patients and methods: Patients who received PEG for enteral nutrition at our hospital between January 2014 and December 2015 were allocated to a postoperative feeding protocol tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 21 publications
1
32
1
Order By: Relevance
“…Nevertheless, this technique is not widely used because the size of the PEG catheter employed is often small. Recently, large-caliber tubes using this technique, such as in our case, can also be safely inserted without increasing the risk of peristomal infection [12]. In our patient, the introducer technique was used along with systemic antimicrobial prophylaxis.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, this technique is not widely used because the size of the PEG catheter employed is often small. Recently, large-caliber tubes using this technique, such as in our case, can also be safely inserted without increasing the risk of peristomal infection [12]. In our patient, the introducer technique was used along with systemic antimicrobial prophylaxis.…”
Section: Discussionmentioning
confidence: 95%
“…Thickened enteral formula is a formula in which viscosity is intentionally increased to prevent enteral nutrition-related complications, such as aspiration pneumonia and diarrhea [12] and has been used mainly in Japan [11]. It has been more than a decade since semi-solid enteral formula was developed but there is limited published literature on this topic despite the wide usage of semi-solid enteral formula in Japan [13]. Semi-solid enteral formula is considered to be more physiologic because swallowed food does not enter the stomach in the liquid form [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been more than a decade since semi-solid enteral formula was developed but there is limited published literature on this topic despite the wide usage of semi-solid enteral formula in Japan [13]. Semi-solid enteral formula is considered to be more physiologic because swallowed food does not enter the stomach in the liquid form [13].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, semi‐solid feeds are often used to deal with feeding‐related adverse events such as aspiration pneumonia, peristomal leakage, and diarrhea in PEG patients. Due to its high viscosity, semi‐solid feed has been reported to reduce the incidence of gastroesophageal reflux and a recent study also showed that it can reduce the risk of aspiration pneumonia in PEG patients …”
Section: Discussionmentioning
confidence: 99%
“…Semi‐solid feeds have been demonstrated to reduce the risk of aspiration pneumonia and shorten postoperative length of stay after percutaneous endoscopic gastrostomy (PEG) . However, the use of semi‐solid feeds via the nasogastric route is difficult in practice due to the high viscosity and only one case report exists in the literature .…”
Section: Introductionmentioning
confidence: 99%